Biosolid amendment of a calcareous, degraded soil in a semi-arid environment - Walter, I.; Martinez, F.; Cuevas, G. (Spanish Journal of Agricultural Research, 2006)
Many soils in the Mediterranean region are subjected to progressive degradation as a result of water erosion. A study was carried out to examine the effects of biosolids on a degraded soil. Single doses of 40, 80 and 120 Mg haE1 of a biosolid were applied to the surface of soil and their effects on its chemical characteristics and on the native vegetation were assessed. Soil macronutrients, micronutrients and heavy metals were tested one and five years after application. Canopy cover, biomass production and mineral composition of native vegetation were also determined. Biosolids increased the content of most nutrients in the soil, although this effect decreased over time. The soil organic matter content did not increase significantly at the beginning of the experiment, although significant differences were observed after five years. The contents of total and extractable heavy metals did not change with time after the application. The native plant biomass production and the canopy cover significantly increased with all the doses applied at the beginning of the experiment, and remained high five years after biosolids application.